Special meeting in Emmeline Pethick-Lawrence's appartment to consider the future of the suffragettes. F.l.t.r.: Christabel Pankhurst, Kenney, Martel, Mrs. Pankhurst, Despard (1906)
Special meeting in Emmeline Pethick-Lawrence's appartment to consider the future of the suffragettes. F.l.t.r.: Christabel Pankhurst, Kenney, Martel, Mrs. Pankhurst, Despard.